PROMOTION MEDIA OF "SNOW" DRINKING WATER - Andrianto, Teguh (Arty: Jurnal Seni Rupa, 2019)
The purpose of this research to produce a promotional media design in the form of pamphlets, uniforms, vehicles, merchandise, stationary sets, company profiles, website design and x-banner for drinking water in SNOW brand packaging in Semarang The design of this promotional media through the stages of the work process with a sequence of preliminary processes which includes the search for ideas, setting the goals of the work, data collection, SWOT analysis, setting the concept of work, and media selection. The pre-production process includes the preparation of tools and idea-seeking strategies. Production includes rough sketches, vectorization, design refinements, advisory counselors and client consultations, and final art. Presentation of works includes printing and exhibition. In the design of promotional media, work analysis is carried out to produce a good promotional media design. The analysis of the work includes several aspects including technical aspects, aesthetic aspects, and communication aspects. By designing promotional media works, it works to increase brand awareness of SNOW bottlenecks in the eyes of consumers, so that it can influence consumers to consume SNOW products. Suggestions that can be put forward, the design of this promotional media can be realized, so as to increase brand awareness and introduce its products on a broader scale